Circulating Concentrations of C-Type Natriuretic Peptides Increase with Sacubitril/Valsartan Treatment in Healthy Young Men. (17th February 2022) - Thonsgaard, Simon; Prickett, Timothy C R; Hansen, Lasse H; Wewer Albrechtsen, Nicolai J; Andersen, Ulrik Ø; Terzic, Dijana; Plomgaard, Peter; Gustafsson, Finn; Goetze, Jens P; Mark, Peter D
Abstract: Background: C-type natriuretic peptide (CNP) is a cardioprotective peptide with high affinity for the ectoenzyme neutral endopeptidase (neprilysin). We aimed to determine whether angiotensin receptor-neprilysin inhibitor treatment acutely affects circulating concentrations of bioactive CNP and its molecular amino-terminal precursor (NT-proCNP). Methods: We included 9 and 10 healthy young men in 2 randomized crossover trials with sacubitril/valsartan vs control (Trial 1) and sacubitril/valsartan and sitagliptin vs sitagliptin (Trial 2). The participants were randomized to a single dose of sacubitril/valsartan (194/206 mg) or control at the first visit 30 min prior to a standardized meal intake. We obtained blood samples at 12 time points over 5 h and measured plasma concentrations of NT-proCNP in both trials and CNP in Trial 2. Results: NT-proCNP concentrations increased 3.5 h after sacubitril/valsartan treatment, and at 4.5 h concentrations were 42% and 65% higher compared with control in Trial 1 and Trial 2, respectively. The total area under the curve (tAUC)15–270 min was 22% higher ( P = 0.007) in Trial 1 and 17% higher with treatment ( P = 0.017) in Trial 2. Concentrations of bioactive CNP followed a similar temporal pattern with an increase of 93% at 4.5 h and a 31% higher tAUC15–270 min compared with control ( P = 0.001) in Trial 2. Conclusions: Sacubitril/valsartan augments circulating concentrations of both bioactive CNP and NT-proCNP in healthy young men. The increase in bioactive CNP is most likely caused by de novo synthesis and secretion rather than diminished breakdown through neprilysin inhibition. ClinicalTrials.gov registration number NCT03717688